Chicken of the Woods (Laetiporus sulphureus species complex) - Brianna Benitez; Claudia Paez; Matthew Smith; Jason A. Smith (EDIS, 2020)
Species in the Laetiporus sulphureus species complex, also known as “chicken of the woods” mushrooms, are wood-decay fungi that cause brown rot within the heartwood of their tree hosts. The common name “chicken of the woods” is given to some species in this group because they are tasty edible mushrooms. Several Laetiporus species have been harvested to use as food colorants, to dye natural products such as wool, and for human consumption. This new 4-page publication of the UF/IFAS Plant Pathology Department, written by Brianna Benitez, Claudia A. Paez, Matthew E. Smith, and Jason A. Smith, describes these fungi as well as their ecology, management, and potential edibility. https://edis.ifas.ufl.edu/pp358